A Effectiveness of Using Moss Plant E-Book With a Scientific Approach to Improve Student Learning Outcomes - Muamar, Abdullah; Retnoningsih, Amin; Anggraito, Yustinus Ulung (Universitas Negeri Semarang)
E-book This moss plant is an alternative learning resource for students to help them understand the concept of the moss plant material because it is presented in a detailed material coverage accompanied by colorful pictures and equipped with videos that can increase student understanding. The development of the moss e-book has been validated by instructional media experts, material experts and teachers at the Semarang City Biology MGMP forum, and it is stated that the moss plant e-book is very suitable for use in the learning process and can improve student learning outcomes.